IDENTITY CONSTRUCTION AS DEPICTED IN AVRIL LAVIGNE'S SONGS LYRICS: AN ANALYSIS OF CHARACTERIZATION USING TRANSITIVITY SYSTEM - Fitri Laela, - (2008)
This research paper entitled The Identity Construction as Depicted in Avril Lavigne's Songs Lyrics: an Analysis of Characterization Transitivity System is a case study in Critical Discourse Analysis (CDA) which is aimed at finding answers to two formulated research questions: the identity construction as depicted in the Avril Lavigne's songs lyrics and the types of processes predominantly used in the text. The data were obtained from six songs lyrics text selected from three albums of Avril Lavigne released. The study employed qualitative principles using Hallidayan's Systemic Functional Grammar and Kress and Van Leeuwen's theories of reading images are used as tools of analysis for analyzing the texts under study. The results show that the identity constructions of Avril Lavigne are varied according to each album released.